Legal Protection for Land Owners Against Land Mafia That Encloses and Cuts Off Access to The Owner’s Land - Ganesha, Isamu Gusti Putu Rai; Wijaya, William; Rianda, Juan Safero (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: Landowners hold the right to use and access their land, including the right-of-way. When land mafia enclose a parcel and block road access, it creates a fundamental legal issue concerning the protection of those rights.Purposes of the Research: This study was conducted to analyze the legal protection for landowners who lost their right-of-way due to the land mafia, who enclosed and closed access to their land in Indonesia, forcing landowners to surrender and sell their land at low prices.Methods of the Research: This research will use normative juridical research, employing both a legal and a conceptual approach.Results Main Findings of the Research: The findings reveal that closing road access by enclosing a land parcel with the intent to coerce the owner into selling their property constitutes an unlawful act subject to both civil and criminal sanctions. Legal protection for landowners is provided through several mechanisms: they may file a civil lawsuit on the grounds of unlawful conduct to seek compensation for damages and restoration of their right-of-way. In addition, the perpetrator (commonly referred to as a land mafia) may also face criminal prosecution for land encroachment, allowing the state to impose penalties aimed at deterring further violations. Through this combination of civil remedies and criminal enforcement, landowners receive both restorative and punitive legal protection.